Observaciones para disminuir la morbimortalidad del actual manejo de la pancreatitis aguda diagnósticada en los pacientes que acudieron a los Hospitales: Manuel Ygnacio Montero IESS Loja y Hospital Docente Isidro Ayora de Loja en el periodo de julio 2010 a julio 2012. - Isquierdo Vásquez, Enrique Agustín (2013)
The present investigation on "COMMENTS TO REDUCE THE CURRENT MANAGEMENT MORBIMORTALITY Acute Pancreatitis DIANOSTICADA IN PATIENTS ATTENDED TO HOSPITALS" YGNACIO MANUEL MONTERO "TEACHING HOSPITAL IESS Loja and" Isidro Ayora "LOJA IN THE PERIOD JULY 2010 TO JULY 2012 " Information was obtained from medical records of patients diagnosed as acute pancreatitis, the universe was 86 patients. Was verified using indices Score, for determining the degree of morbidity and mortality in patients with pancreatitis and see what kind of therapeutic approach was used, with the following results: Of 86 patients, 52 were female equivalent to 60.5% and 34 men being 39.5%, the most frequent age was <55 years to 66.3%, from 55 to 70th with 19.8% and> 70 years 13.9%. The most frequent causes were gallstones in 54.7%, 15.1% alcohol, 11.6% idiopathic, metabolic, 12.8%, 3.5% and mechanical aggression anatomical lesions 2.3%. As for mortality was 4.7% and morbidity was 22.1%. The Balthazar scale was used in 68.7 to 100%, APACHE II in 71.7%, RANSON 10.4% at admission and 48 h in 1.5%, GLASGOW not used. The NPO was used in 100%, with 60 to 70cc/kg/h Hydration by 84.9%, correction of electrolyte occurred in 22.1%. The NPT was used by 16.3%, analgesia by 50% was used metamizol and 50% used other analgesics; omeprazole was used in 77.9% and 22.1% ranitidine. Prophylactic antibiotics were used in 55.2% to 63.2% and as for ERCP papillotomy requested more by 23.3% and cholecystectomy was performed in 1.2%.